Depression symptoms, anxiety, stress and related factors in medical students - Carbonell, Dayana; Cedeño Arevalo, Susy Vanessa; Morales, Monica; Badiel Ocampo, Marisol; Cepeda, Ivan Leonardo (Interdisciplinary Journal of Epidemiology and Public Health, 2019)
Introduction: Mental health is a serious public health problem, a high prevalence of depressive symptoms, anxiety and stress is reported in medical students.Objective: To identify the frequency and determinants of mental health problems of medical students at a university in 2018.Methods: Cross-sectional study with 813 medical students at a university in Cali-ColombiaResults: The prevalence of depression was 31.7%, anxiety (59.9%), and stress (37.3%). 64.4% were women, the average age was 21.9 ± 3.6 years. The variables that explain independently of presenting mental illness were: male sex OR: 0.48 (95% CI: 0.36-0.65), number of hours of weekly class OR: 1.01 (95% CI: 1.0-1.02) for anxiety, career satisfaction OR: 0.61 (95% CI: 0.39-0.97). As a protective factor for depression, sports hours in week to variables depression OR: 0.95 (95% CI: 0.91-0.99), anxiety OR: 0.95 (95% CI: 0.92-0.98), and, stress OR: 0.91 (95% CI: 0.88-0.95).Conclusions: The study found high prevalence of mental illness in medical students that can be explained by sex, number of hours of weekly class, satisfaction with the race and weekly sports hours. Key words: depression, anxiety, stress, sociodemographic variables.